THE STRATEGY of ECONOMIC DEVELOPMENT REGION BASE on THE LEADING SECTOR at KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Desi Novita; Hartono Gultom (JASc (Journal of Agribusiness Sciences), 2017)
Economic development is an absolute process undertaken by a nation in improving the lives and welfare of the entire nation. Economic development that refers to the leading sectors will have an impact on the acceleration of economic growth. This research is done to determine the strategy and policy direction suitable to build the leading sector of langkat regency in order to increase economic growth of langkat regency.in the previous research it was found that the leading sector of langkat regency was agriculture forestry and fishery sector. The analysis method used in this research is descriptive SWOT analysis. Obtained some strategiest that are considered suitable for the development of agriculture forestry and fishery sector as the leading sector of langkat regencyKeyword : SWOT, leading sector, regional economic development